2021
DOI: 10.1186/s12894-021-00942-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of premature ejaculation and its relationship with polygamous men: a cross-sectional observational study at a tertiary hospital in Somalia

Abstract: Background Premature ejaculation (PE) is the most common and prevalent sexual disorder among men. To the best of our knowledge, this is the first study aimed at evaluating the relationship of PE among polygamous men. Method Over a 1-year period, a cross-sectional observational study was carried out among 202 married men who visited the urology polyclinic due to different clinical conditions and contributed by completing a standardized structured qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Overall, 27 studies including 62,809 subjects with a mean age of 45.2 ± 9.5 years were included in the analysis ([ 5 , 15 41 ], Table 2 ). Among them 13,026 (20.7%) reported PE which was defined according to different criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, 27 studies including 62,809 subjects with a mean age of 45.2 ± 9.5 years were included in the analysis ([ 5 , 15 41 ], Table 2 ). Among them 13,026 (20.7%) reported PE which was defined according to different criteria.…”
Section: Methodsmentioning
confidence: 99%
“…14 Over the last 20 years, epidemiological studies/surveys of various populations have found the prevalence of PE in men to be 20%-33%, 10,15,16 whilst others more recently have estimated it to be as high as 50%. 17,18 Retrograde ejaculation refers to a partial or complete lack of antegrade seminal fluid produced on ejaculation, and unlike PE, it almost always has an organic cause. It is probably the next most common ejaculatory disorder reported by diabetic men after PE.…”
Section: Definitionsmentioning
confidence: 99%
“…Premature Ejaculation is frequently reported as the most common sexual disorder in men 14 . Over the last 20 years, epidemiological studies/surveys of various populations have found the prevalence of PE in men to be 20%–33%, 10,15,16 whilst others more recently have estimated it to be as high as 50% 17,18 …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, According to the Diagnostic and Statistical Manual of Mental Disorders, premature ejaculation (PE) is a condition where "Ejaculation occurring, without control, on or shortly after penetration and before the person wishes it, causing marked distress or interpersonal difficulty" [5] . Affecting 30%-50% of males, PE is the most widespread and common sexual condition in men [6] . Another form of MSD is decreased libido, which means "reduction in sex drive".…”
Section: Introductionmentioning
confidence: 99%